Pengaruh Pertumbuhan Ekonomi, DAU, DAK, PAD Terhadap Indeks Pembangunan Manusia dengan Pengalokasian Anggaran Belanja Modal Sebagai Variabel Intervening (Studi Empiris pada Pemerintah Kabupaten dan Kota se-Jawa Tengah) - Setyowati, Lilis; Suparwati, Yohana Kus (PRESTASI, 2012)
The implementation of fiscal decentralization in addition to give authority to local goverments in the region also affects the ability of the local potentials to allocate revenues to fulfill the public interest, and enhance public welfare. The public welfare can be seen  from the increasing of Human Development Index of the region through the allocation of capital expenditures. This study aims to prove empirically that Economic Growth (represented by PDRB), the General  Allocation Fund (DAU), the Special Allocation Fund (DAK), Local Revenue (PAD) affect Human Development Index over the Allocation of Capital Expendicture Budget (PABM) which is represented by Capital Expenditure. The sampling method used in this study is purposive sampling, with total samples of 22 regencies and 3 cities from the population of 35 regencial governments  in Cetral Java during 2005-2009. The analysis used is multiple linear regression for the first step model and simple linear regression for the second step model. The result of statistical test from the first step model showed that Economic Growth negatively affect  PABM. While DAU, DAK, PAD positively affect to PABM. The result of statistical tests from the second step model showed the presumption of PABM positively influences on IPM. Based on path analysis showed that only the Economic Growth that has no effect on IPM through PABM, while DAU, DAK, and PAD affect IPM through PABM. Adjusted R square value obtained for each model of the research in the first step model of 53,5% and 3,1% for the second step model.Keywords :           Economic Growth, General Allocation Fund (DAU), Special Allocation Fund (DAK), Local Revenue (PAD), Capital Expenditures, and the Human Development Index (IPM).